TANGGUNG JAWAB NOTARIS ATAS DOKUMEN DIBAWAH TANGAN YANG DIBERI TANDA (WAARMERKING) YANG TANDA TANGANNYA DIPALSUKAN OLEH PARA PIHAK. - Entin, Entin; Halim, Anriz Nazaruddin; Ridwan, Rifki (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to explore the responsibilities of notaries in relation to documents under signed hands (waarmerking), particularly in contexts where signatures on such documents are forged by the parties. where tried to answer the question,